KELENGKAPAN DAN KETEPATAN WAKTU PENGISIAN RESUME MEDIS ≤1X24 JAM OLEH DOKTER DI RSIA SMB TAHUN 2020 - Savitri, Febriana; Putri, Septiara (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2023)
The discharge summary is a resume of all patient care and treatment periods that must be filled in entirely by the doctor in charge within 1x24 hours after the patient is pronounced discharged. This study examines the completeness and timeliness of filling in discharge summaries by using the system approach. This research is a qualitative study to obtain input and transformation through in-depth interviews and review of hospital documents, then reinforced with quantitative research to get an overview of the output through observation and study of discharge summary forms. Sixty one discharge summary forms were used as research samples by calculating total sampling. The results showed that the percentage of discharge summaries included in the category fulfilled was only 16.4%. At the same time, in terms of timeliness, it was found that only 45.9% of filling discharge summaries were included in the appropriate time accuracy category. The average time needed for a doctor to get a discharge summary is 32.3 hours. The patient identity and the nursing data items group had the lowest filling distribution, while the highest was in the medical data and data authentication group. There are still differences in knowledge in filling out discharge summary, lack of motivation of the doctors, form formats evaluation that has not been carried out routinely; there is no reward system, punishment system and special training for discharge summary, differences in perceptions regarding the flow of the discharge summary filling process, and the discovery of conflicts related to communication.